2010
DOI: 10.2174/157488910793362412
|View full text |Cite
|
Sign up to set email alerts
|

Current Options in the Treatment of Mitochondrial Diseases

Abstract: Mitochondrial diseases (MD) are disorders caused by an impairment of the mitochondrial respiratory chain function. They are usually progressive, isolated or multi-system diseases and have variable times of onset. Because mitochondria have their own DNA (mtDNA), MD can be caused by mutations in both mtDNA and nuclear DNA (nDNA). The complexity of genetic control of mitochondrial function is in part responsible for the intra- and inter-familiar clinical heterogeneity of this class of diseases. Despite the remark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 76 publications
0
17
0
Order By: Relevance
“…Interestingly, it has been reported that CoQ 10 inhibits NLRP3-inflammasome activation in patients with FM 12. Furthermore, MitoQ, a mitochondria-targeted derivative of CoQ 10 , has also been reported to inhibit NLRP3-inflammasome 54. As CoQ 10 is a common treatment for mitochondrial diseases,30–32 55 56 here, we report another potential mechanism by which CoQ 10 treatment can be effective in these patients.…”
Section: Discussionmentioning
confidence: 61%
“…Interestingly, it has been reported that CoQ 10 inhibits NLRP3-inflammasome activation in patients with FM 12. Furthermore, MitoQ, a mitochondria-targeted derivative of CoQ 10 , has also been reported to inhibit NLRP3-inflammasome 54. As CoQ 10 is a common treatment for mitochondrial diseases,30–32 55 56 here, we report another potential mechanism by which CoQ 10 treatment can be effective in these patients.…”
Section: Discussionmentioning
confidence: 61%
“…This is of particular importance as mitochondrial dysfunction, ROS and apoptosis have been linked to several human conditions such as aging, cancer 100, diabetes 101102 and non-alcoholic steatohepatitis 103, but also neurodegenerative disorders 104 including Alzheimer disease 105 and Parkinson’s disease 106107, and rare diseases such as WD 4. Current treatment options for mitochondrial dysfunction-related disorders are inadequate and mostly consist of the administration of cofactors and oxygen radical scavengers 108109110. Thus, there still is an urgent need for novel treatments in combating mitochondrial dysfunction-related disorders and ARBs may show promise, as well as OSIP108, in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…They are essential in the support of mitochondrial function by providing antioxidants, cofactors, metal ions, salts, and other molecules that are essential in supporting the functions of mitochondrial enzymes, electron transport systems, mtDNA replication, fat and sugar metabolism, protein synthesis and proper antioxidant balance [296][297][298]. Vitamins, such as B (multiple), D, E, C, and ions, such as iron, magnesium, manganese, zinc, among other small molecules, are important n this regard, and up to one-half of the aging North American population is deficient in these vitamins, minerals and other micronutrients [299].…”
Section: Vitamins and Mineralsmentioning
confidence: 99%
“…The use of micronutrients in helping to restore and/or maintain mitochondrial function has proven useful in consert with other treatment modialties [296,298,300]. Although there are few clinical trials in the literature that demonstrate the usefulness and utility of supplementation with only vitamins, minerals, antioxidants and other micronutrients alone in supporting mitochondrial function, the ones that have been conducted clearly show the importance of providing adequate oral doses of vitamins, minerals, antioxidants and other micronutrients to maintain mitochondrial energy functions [296.…”
Section: Vitamins and Mineralsmentioning
confidence: 99%